Crystalglobulinemia manifesting as chronic arthralgia and acute limb ischemia: A clinical case report. Issue 16 (April 2017) - Abe, Nobuya; Tomita, Tomoko; Bohgaki, Miyuki; Kasahara, Hideki; Koike, Takao
Abstract: Rationale: Crystalglobulinemia is a rare disease caused by monoclonal immunoglobulins, characterized by irreversible crystallization on refrigeration. It causes systemic symptoms including purpura, arthralgia, and vessel occlusive conditions to be exacerbated by exposure to cold. We report a patient with crystalglobulinemia associated with monoclonal gammopathy of undetermined significance (MGUS) manifesting as chronic arthralgia and recurrent acute arterial occlusion. Presenting concerns: A 61-year-old man, who had been diagnosed with MGUS and who had arthralgia of unknown origin, presented with recurrent acute limb ischemia after surgical thromboembolectomy. Refrigeration of his serum formed precipitates that looked like needle-shaped crystals. These crystals did not dissolve with warming, which is not a characteristic of cryoglobulins. Skin biopsy results showed crystal-liked eosinophilic bodies in small vessels and we diagnosed crystalglobulinemia. Intervention and outcomes: Although he underwent above-knee amputation, he was treated with a bortezomib and dexamethasone-based chemotherapeutic regimen, following lenalidomide maintenance therapy. Finally, he achieved complete remission and serum crystalglobulins diminished. Lessons: Monoclonal gammopathy, previously diagnosed as MGUS, can cause systemic symptoms and thrombotic conditions by producing pathologic immunoglobulins, such as crystalglobulins. In such situations, MGUS, even when it has not progressed to multiple myeloma, can be a target of aggressive chemotherapy. Crystalglobulinemia should be considered for patients with monoclonal gammopathy manifesting as systemic and thrombotic symptoms exacerbated by cooling.